DESIGNING PAV (PASSIVE AND ACTIVE VOICE) BOARD AS A MEDIUM FOR LEARNING PASSIVE AND ACTIVE VOICE FOR THE ELEVENTH GRADE STUDENTS - Irma Nur Asyifa; Yanti Sri Rezeki; Dwi Riyanti; Urai Salam; Surmiyati Surmiyati (PROJECT (Professional Journal of English Education), 2023)
Media can be used as an aid in supporting teaching and learning English at school. However, there are still a few media variations used to deepen the student’s understanding of the material. This study aimed to design PAV (Passive and Active Voice) Board as a medium to help students in Grade XI of SMAN 10 Pontianak learn and deepen their understanding of passive and active voice. This study used ADDIE as the research model with three phases: Analysis, Design, and Development. The data were collected by distributing the need analysis questionnaire to the 31 students in Grade XI IPS 1 of SMAN 10 Pontianak and an internal evaluation questionnaire to an English teacher of SMAN 10 Pontianak. The finding showed that students need a medium that can support them in learning passive and active voice which are changing active voice into passive voice, remembering the formula passive and active voice, identifying the subject, to be, verb 1, verb 2, verb 3, object, object pronoun, and preposition, and for PAV Board as a medium had a good score from the evaluator in criteria of the content, language, visual appearance, and product guide, which is 3.61 that categorized as "Strongly Worth”. In conclusion, designing PAV Board as a medium for learning passive and active voice was appropriate.